EFFECTIVENESS ONLINE LERNING AMONG STUDENTS WITH DISABILITIES - Muhamad Amirul Amin Adnan; Nur Syazwani Mohd Nawi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Education is one of the most important aspects for every individual including those students with disabilities. Students with disabilities also have the right to get a good education and the opportunity to go to higher education. Accordingly, this article examines the challenge. This study uses a full qualitative approach, a case study at the University of North Malaysia (UUM). In-depth interviews were used in data collection involving 12 students with disabilities. The findings show that among the main challenges faced by disabled students who follow online learning are Isolation, emotional regression, Declining Mental State, Internet interference, Emotions and less conducive environment and Lack of Self-Assurance to Enroll in Online Classes. besides that, there are various suggestions in improving the challenges of online learning for students with disabilities at university. In conclusion, this study emphasizes the challenges and suggestions in improving the challenges of effectiveness online learning for students with disabilities at university so that appropriate support and facilities can be provided by the university effectively.